2020
DOI: 10.1111/faf.12460
|View full text |Cite
|
Sign up to set email alerts
|

Something old, something new: Historical perspectives provide lessons for blue growth agendas

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 84 publications
3
49
0
Order By: Relevance
“…3). Prior research has shown that development based on living marine resources-including blue carbon, ecotourism, fishing and mariculture-can be important at local scales but may not be ecologically sustainable or socially desirable at larger scales 3,4 . In these cases, stakeholders may feel misled by growth projections revealed to be unattainable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Prior research has shown that development based on living marine resources-including blue carbon, ecotourism, fishing and mariculture-can be important at local scales but may not be ecologically sustainable or socially desirable at larger scales 3,4 . In these cases, stakeholders may feel misled by growth projections revealed to be unattainable.…”
Section: Discussionmentioning
confidence: 99%
“…We find that the key differences in the capacity of regions to achieve a blue economy are not due to available natural resources, but include factors such as national stability, corruption and infrastructure, which can be improved through targeted investments and cross-scale cooperation. Knowledge gaps can be addressed by integrating historical natural and social science information on the drivers and outcomes of resource use and management, thus identifying equitable pathways to establishing or transforming ocean sectors 1,3,4 . Our results suggest that policymakers must engage researchers and stakeholders to promote evidence-based, collaborative planning that ensures that sectors are chosen carefully, that local benefits are prioritized, and that the blue economy delivers on its social, environmental and economic goals.…”
mentioning
confidence: 99%
“…The suggested OBP framework allows to promote public engagement by giving a voice to local communities and will also provide recommendations for policy makers, research institutions, international organizations, NGOs, business leadership and civil society to address systemic aspects of inequities along a spectrum of ambitions, from basic to transformative. Finally, the OBP framework can be easily scalable and operationalized to be used in different geographical areas at local and international levels to promote blue economy and ocean equity (Caswell, Klein, Alleway, et al, 2020). ACKNOWLEDGMENTS A.…”
Section: Discussionmentioning
confidence: 99%
“…Historical and current trajectories for land and coastal systems show that often these actions have not been proactively undertaken to the extent needed (e.g. Caswell et al 2020 ). This has resulted in over-industrialisation and depletion, which are conditions difficult to reverse.…”
Section: Pathway Towards a More Sustainable Offshore Blue Economymentioning
confidence: 99%